Regulation of Protein Synthesis at the Translational Level: Novel Findings in Cardiovascular Biology - Sergey Tsoy; Jiandong Liu (Biomolecules)
Translational regulation plays a pivotal role in cardiac gene expression, influencing protein synthesis in response to physiological and pathological stimuli. Although transcription regulates gene expression, translation ultimately determines protein levels, making it a crucial research focus. In cardiomyocytes, disruptions in this process contribute to various cardiac diseases, including hypertrophy, fibrosis, dilated cardiomyopathy, ischemic heart disease, and diabetic cardiomyopathy. Emerging evidence highlights the significance of translational regulation across multiple cardiac cell types, such as cardiomyocytes and fibroblasts, and its role in disease progression. During cardiac remodeling, transcriptomic changes are often modest, suggesting that post-transcriptional mechanisms, particularly translation, play a dominant role in cellular adaptation. This review discusses key methodologies for studying translational regulation and novel mechanisms of translational regulation related to different cardiac pathologies and highlights relevant therapeutic avenues for targeting these pathways.